Misleading presentation of a ruptured renal angiomyolipoma - Mazlan, Sakinah; Abd Wahab, Nyazirah; Mohd Ghani, Khairul Asri; Ab. Hamid, Suzana (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
We report a case of a 37-year-old pregnant lady at 27 weeks of gestation presented with contraction pain mimicking abruptio placenta. She developed hypovolemic shock six hours following hospital admission. Subsequent emergency caesarian section revealed a viable fetus with retroperitoneal hematoma but no evidence of placenta abruption. Post-operative abdominal CT angiography demonstrated a ruptured and bleeding left renal mass with fatty component consistent with renal angiomyolipoma. In view of the patient’s clinical condition who was persistently critical, an emergency left nephrectomy was proceeded which confirmed the diagnosis of a ruptured left renal angiomyolipoma intraoperatively and histologically.